Sidescan sonar survey (300 kHz) during R/V Heincke cruise HE502 in the German Bight with link to raw data files - H Christian Hass; Svenja Papenmeier (PANGAEA, 2019)
Sidescan sonar data were collected during R/V Heincke cruise HE502 with a towed multi pulse Edgetech 4200-MP. Data recording was executed along 16 parallel profiles in North Sea within German EEZ. The survey speed was ~5 knots and the swath set to 460 m to obtain a resolution of ~1 m along track. The track distance is 400 m. In total 350 km^2 were area-wide mapped. The interpreted sediment distribution map of this data area published in the GeoSeaPortal of the Federal Maritime and Hydrographic Agency (Papenmeier, S., Hass, H.C., Propp, C., Thiesen, M., Zeiler, M.: Verteilung der Sedimenttypen auf dem Meeresboden in der deutschen AWZ (1:10.000). www.geoseaportal.de, 2018).